The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1128/jvi.01471-09
|View full text |Cite
|
Sign up to set email alerts
|

Associations between HLA Class I Alleles and Escape Mutations in the Hepatitis B Virus Core Gene in New Zealand-Resident Tongans

Abstract: The full repertoire of hepatitis B virus (HBV) peptides that bind to the common HLA class I molecules found in areas with a high prevalence of chronic HBV infection has not been determined. This information may be useful for designing immunotherapies for chronic hepatitis B. We identified amino acid residues under positive selection pressure in the HBV core gene by phylogenetic analysis of cloned DNA sequences obtained from HBV DNA extracted from the sera of Tongan subjects with inactive, HBeAg-negative chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 32 publications
(48 reference statements)
4
29
0
Order By: Relevance
“…A study from New Zealand reported that, in the core protein, S21 was one of the amino acids under significant positive selection pressure. 34 These data suggested that the S21 substitution favors the persistence of HBV in the late stage of the natural course of HBV chronic infection, despite the developed immunity.…”
Section: Discussionmentioning
confidence: 93%
“…A study from New Zealand reported that, in the core protein, S21 was one of the amino acids under significant positive selection pressure. 34 These data suggested that the S21 substitution favors the persistence of HBV in the late stage of the natural course of HBV chronic infection, despite the developed immunity.…”
Section: Discussionmentioning
confidence: 93%
“…Associations between HLA class I genotypes/alleles and escape mutations in the HBV core gene have been investigated in chronic HBV infection (40,41). However, associations of HLA-DP polymorphisms with HBV mutations have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of New Zealand Tongans with chronic hepatitis B (CHB) with known specific HLA types (mainly HLA-B*4001 and HLA-B*5602 in patients with genotype C and D infections), 13 sites in the HBV genome under significant positive selection pressure were identified, and 5 of these sites were associated with a specific HLA type (1). One of these significant associations was between HLA-B*4001 and position 106 (equivalent to position 77 in reference 1), the same association found in our cohort, but by use of a different approach, identifying adaptation rather than selection.…”
Section: Discussionmentioning
confidence: 99%